2020
DOI: 10.1002/jat.4128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dibenzothiophene, a sulfur‐containing heterocyclic aromatic hydrocarbon, and its alkylated congener, 2,4,7‐trimethyldibenzothiophene, on placental trophoblast cell function

Abstract: Worldwide demand for petroleum products has resulted in increased oil and gas activities in many countries. Conventional and unconventional oil and gas extraction, production, and transport lead to increased levels of petroleum‐derived polycyclic aromatic hydrocarbons (PAHs) in the environment. PAH exposure has profound effects on reproduction by affecting pathways involved in placental trophoblast cell function and impairing normal placental development and function—key contributors to reproductive success. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Interestingly, however, the observed effects were influenced by alkylation ( Lee et al, 2017 ). Similarly, another study conducted in human placental trophoblast cells reported that the alkylated congener of a petroleum-derived S-containing heterocyclic PAC, 2,4,7-trimethyldibenzothiophene, but not its parent compound dibenzothiophene, significantly increased E2 secretion in association with surrogate markers for angiogenesis ( Raez-Villanueva et al, 2021 ).…”
Section: Effect Of Pacs On Ovarian Hormone Secretion and Angiogenesismentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, however, the observed effects were influenced by alkylation ( Lee et al, 2017 ). Similarly, another study conducted in human placental trophoblast cells reported that the alkylated congener of a petroleum-derived S-containing heterocyclic PAC, 2,4,7-trimethyldibenzothiophene, but not its parent compound dibenzothiophene, significantly increased E2 secretion in association with surrogate markers for angiogenesis ( Raez-Villanueva et al, 2021 ).…”
Section: Effect Of Pacs On Ovarian Hormone Secretion and Angiogenesismentioning
confidence: 95%
“…There is considerable evidence that PACs can function as EDCs and negatively affect reproductive function ( Bolden et al, 2017 , Khan et al, 2021 ; Lee et al, 2017 , Raez-Villanueva et al, 2021 ; Zhang et al, 2016 ). However, reports on the impacts of PACs on the ovary in mammals are limited.…”
Section: Effect Of Polycyclic Aromatic Compounds (Pacs) On Ovarian De...mentioning
confidence: 99%